Why Do Women Skip Fasting During Their Period? Integrating Curriculum Ibadah with a Women’s Perspective and the Reinterpretation of Menstruation (Haid) - Muthmainnah, Yulianti (Salasika, 2025)
Why Do Women Skip Fasting During Their Period? Integrating Curriculum Ibadah with a Women’s Perspective and the Reinterpretation of Menstruation (Haid). This study examines how female students at the Ahmad Dahlan Institute of Technology and Business Jakarta understand menstruation in relation to the practice of fasting and other acts of worship, which is based on coursework on campus. This study departs from controversies on social media between 2019 and 2020 concerning the permissibility of fasting for menstruating women. This qualitative research employs a grounded theory approach and collects primary data through in-depth interviews as well as open discussions in classroom learning and Gender Equality and Reproductive Health training. The respondents were aged 17–25 years and had backgrounds of activity in two categories, namely those merely active in the organization, and those active in the organization and have involvement in gender studies and women’s movements. The results show that first, female students who argue that menstruating women may fast or perform other acts of worship are considered liberal and as opposing the word of Allah Swt and the Qur’an. Second, female students who have not been involved in women’s movements tend to view the prohibition of fasting and other acts of worship as a rule based on the assumption that menstruation is “impure.” Third, respondents who are active in gender studies and women’s movements argue that fasting during menstruation may be permitted depending on a woman’s condition, and they reject the assumption that menstruation is something impure.